BURNOUT AMONG ANAESTHESIOLOGISTS IN INDIA. A QUESTIONNAIRE BASED STUDY - JOHN, ANNIE SHEEBA; KUMAR T, SENTHIL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Small acute stress events occurring every day at work, can gradually lead to long-term, chronic stress. Burnout syndrome is the response to chronic occupational stress experienced by the person. We aimed to assess the prevalence of burnout among practicing anaesthesiologists in India and its association with personal and professional characteristics. Methods: A cross-sectional survey study was conducted, wherein a questionnaire was emailed to 5000 anaesthesiologists. An anonymous self-administered questionnaire consisting of socio-demographic, career, and work conditions, and Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was used. Data were analysed according to the guidelines for data processing with SPSS and an analysis of the scales used. Results: There were 1238 responders, with a response rate of 24.7%. A total of 864 completed responses were considered for analysis. The prevalence of emotional exhaustion, depersonalisation, and low professional outcome among our responders was 39.5%, 65%, and 50.6%. Senior residents showed a high prevalence of burnout in all subsets compared to other designation (p < 0.001). Increased prevalence was seen in the 26–35 years age group, those working around 12 h/day, doing 7–10 night shifts per month, and perceived poor remuneration. Conclusion: We conclude, that chronic stress and burnout are prevalent among anaesthesiologists in India at alarming levels. Coping strategies and relaxation techniques are necessary to reduce burnout and increase work efficiency.